Analisis Audit Internal dalam Pengelolaan Dana Pondok Pesantren: Studi Kasus di Pondok Pesantren Ikhya’ Birrulwalidain - Binti Salisatul Mahbubah; Fatma Eldayena; Depi Putri Erliya; Fikri Rizki Utama (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the role of internal audit in fund management at Pondok Pesantren Ikhya’ Birrulwalidain using a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving the head of the Islamic boarding school, the treasurer, and administrative staff. The findings indicate that internal audit practices are implemented through regular supervision of financial recording, financial reporting, and the use of operational funds. Internal audit strengthens financial discipline and enhances transparency and accountability in fund management. Financial evaluations are conducted periodically through internal coordination meetings, which support more effective oversight and help reduce the risk of financial irregularities. However, several challenges remain, including limited human resources with adequate accounting and auditing competencies, the absence of standardized written operational procedures, and the continued use of manual financial recording systems. These conditions affect the overall effectiveness of internal audit implementation. The study concludes that internal audit plays a crucial role in improving financial governance in Islamic boarding schools. Strengthening human resource capacity, establishing standardized audit procedures, and adopting digital financial management systems are essential strategies to improve audit effectiveness and ensure sustainable fund management.